Investigating the Work of School Based Religious Education Leaders in Australian Catholic Schools - Rymarz, Richard (Religious education, 2022)
The aim of this research was to get a better understanding of the work of school-based religious education leaders (SBREL) by examining the issues and challenges they face as well as how they are supported. SBREL were surveyed and interviewed, and they took part in focus groups. SBREL, in general, felt supported in their role. A major issue identified by SBREL was the implications of the changing demographics of Catholic schools, marked by growing numbers of non-Catholic students and weakening religious affiliation. Several challenges were identified. These included making Religious Education (RE) more engaging, the need for more practical assistance in delivering the RE curriculum, and providing better ongoing formation for teachers to better equip them to teach RE.